Fostering community, sharing power: Lessons for building restorative justice school cultures - Sandwick, Talia; Hahn, Josephine Wonsun; Hassoun Ayoub, Lama (Education Policy Analysis Archives, 2019)
Increasingly, education policymakers are touting restorative justice as a way to interrupt the “school-to-prison pipeline,” which disproportionately impacts students by race, sexuality, and disability. A small but growing research literature suggests that restorative justice decreases suspension and behavioral incidents, while improving school climate—particularly when embraced as a schoolwide ethos, rather than a targeted disciplinary strategy. Restorative justice represents a marked departure from long-standing punitive approaches to discipline, however, and school communities are eager for support in navigating this culture shift. To this end, this article presents findings from case studies of five diverse NYC schools using restorative justice approaches. Drawing on qualitative data from interviews and focus groups with educators, students, parents, and school safety agents, our findings provide insight into key practices and resources, stakeholder perceptions, and challenges of and practical strategies for building holistic, schoolwide restorative justice. We present a series of “lessons” to inform restorative justice practice and policy, underscoring the importance of community-building, deliberate resources and infrastructure, interrogating localized and systemic power dynamics, and elevating student leadership.